Proceedings of the 12th International Conference on Advances in Mobile Computing and Multimedia 2014
DOI: 10.1145/2684103.2684134
|View full text |Cite
|
Sign up to set email alerts
|

A Vehicle Speed Estimation Mechanism Using Handovers and Call Arrivals of Cellular Networks

Abstract: Information and communication technologies have improved the quality of Intelligent Transportation Systems (ITS). The real-time traffic information has traditionally been collected via stationary vehicle detectors or GPS-based probe cars. Compared to the traditional ways, estimating traffic information from Cellular Floating Vehicle Data (CFVD) is more cost-effective, and easier to acquire. In this paper, this study proposes a novel approach to evaluate the relation of call arrival, handover, traffic flow, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…A method was proposed to retrieve the NLU events, which were triggered when MSs entered a new location area, and to estimate traffic flow in accordance with the amount of NLU events [24]. For traffic density estimation, a method was proposed to monitor the CA events and to analyze the relationship between traffic density and the amount of CA events [25]. These studies indicated that their proposed methods can estimate traffic information precisely with anonymous MSs.…”
Section: Signal Statisticsmentioning
confidence: 99%
See 4 more Smart Citations
“…A method was proposed to retrieve the NLU events, which were triggered when MSs entered a new location area, and to estimate traffic flow in accordance with the amount of NLU events [24]. For traffic density estimation, a method was proposed to monitor the CA events and to analyze the relationship between traffic density and the amount of CA events [25]. These studies indicated that their proposed methods can estimate traffic information precisely with anonymous MSs.…”
Section: Signal Statisticsmentioning
confidence: 99%
“…The process is called a handover from Celli−1 to Celli. This study assumes that the call holding time (t) is exponentially distributed with the mean 1/ μ to generate handovers [25]. The average speed of cars is Ui, and the traffic flow is Qi.…”
Section: Traffic Flow Estimation By Using Ho Eventsmentioning
confidence: 99%
See 3 more Smart Citations